2015
DOI: 10.3892/or.2015.4133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of daidzein in regards to cytotoxicity in vitro, apoptosis, reactive oxygen species level, cell cycle arrest and the expression of caspase and Bcl-2 family proteins

Abstract: In the present study, the in vitro cytotoxicity of daidzein was evaluated in human BEL-7402, A549, HeLa, HepG-2 and MG-63 cancer cell lines. BEL-7402 cells were sensitive to daidzein treatment, with an IC50 value of 59.7±8.1 µM. Daidzein showed no cytotoxic activity toward A549, HeLa, HepG-2 and MG-63 cells. Daidzein increased the levels of reactive oxygen species (ROS) and induced a decrease in mitochondrial membrane potential. Morphological and comet assays showed that daidzein effectively induced apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 12 publications
4
17
0
1
Order By: Relevance
“…As A549 line has been widely used as a model system to study human alveolar carcinoma, cytotoxic profile of flavonoids in these cells was previously characterized with the results very similar to those measured in our work. Indeed, the IC 50 value of 72.2 µM for quercetin is close to the inhibitory constants published by Loizzo et al (26), Tan et al (27)(28)(29), Robaszkiewicz et al (30), and Chan et al (31); and IC 50 values more than 100 µM were previously reported for fisetin (32), hesperetin (33-35), luteolin (32,36), chrysin (35), baicalein (34), daidzein (37), and genistein (38). Based on our results presented in this article, cytotoxic activity profiles of flavonoids were rather similar for both A549 and HCC-44 lung cancer lines, despite the gender difference of initial origin of these cells.…”
Section: Discussionsupporting
confidence: 86%
“…As A549 line has been widely used as a model system to study human alveolar carcinoma, cytotoxic profile of flavonoids in these cells was previously characterized with the results very similar to those measured in our work. Indeed, the IC 50 value of 72.2 µM for quercetin is close to the inhibitory constants published by Loizzo et al (26), Tan et al (27)(28)(29), Robaszkiewicz et al (30), and Chan et al (31); and IC 50 values more than 100 µM were previously reported for fisetin (32), hesperetin (33-35), luteolin (32,36), chrysin (35), baicalein (34), daidzein (37), and genistein (38). Based on our results presented in this article, cytotoxic activity profiles of flavonoids were rather similar for both A549 and HCC-44 lung cancer lines, despite the gender difference of initial origin of these cells.…”
Section: Discussionsupporting
confidence: 86%
“…65 For MDA-MB-231, in turn, the effect of the isoflavone is less marked, and does not appear to change significantly for concentrations above 50 µM. 52…”
Section: C3 Ros/rns Measurementmentioning
confidence: 95%
“…It has been reported that Bim plays an important role in cell apoptosis (35)(36)(37). To investigate the potential role of Bim protein in the process of TAM-induced apoptosis, we further determined the Bim expression in TAM-sensitive MCF-7 cells (MCF-7) and TAM-resistant MCF-7 cells (MCF-7R) by Q-PCR and western blot analyses.…”
Section: Bim Is a Pro-apoptosis Effector Of Tam-induced Apoptosis Inmentioning
confidence: 99%